The effects of perceived discrimination, social support and ethnic identity on mental health of immigrant adolescents - Ergin Derya Atalan (Scandinavian Journal of Child and Adolescent Psychiatry and Psychology, 2021)
Background: The number of immigrants has been increasing. Immigrant adolescents experience an acculturation process that affects particularly their ethnic identity, perceived discrimination, and relationships with their peers, which would have significant impact on their mental health. The ethnic composition of social environments might affect this relationship.